Cognitive dysfunction in central disorders of hypersomnolence: A systematic review. (October 2021) - Filardi, Marco; D'Anselmo, Anita; Agnoli, Sergio; Rubaltelli, Enrico; Mastria, Serena; Mangiaruga, Anastasia; Franceschini, Christian; Pizza, Fabio; Corazza, Giovanni E.; Plazzi, Giuseppe
Summary: Central disorders of hypersomnolence (CDH) are characterized by excessive daytime sleepiness not related to comorbid sleep or medical disturbances. We systematically examined scientific literature on cognitive functions in patients suffering from CDH. Forty-eight studies proved eligible and were analyzed separately for Narcolepsy Type 1 (NT1), Narcolepsy Type 2 (NT2), Idiopathic hypersomnia (IH) and Kleine-Levin syndrome (KLS). Results were grouped into the cognitive domains of attention, memory, executive functions and higher order cognition. Consistent attention impairments emerged in NT1, NT2 and IH patients, with NT1 patients showing the most compromised profile. Memory functions are largely unimpaired in CDH patients except for KLS patients who display memory deficit. Executive functions and higher-order cognition have been assessed in NT1 while they received little-to-no attention in the other CDH. NT1 patients display high performance in executive functions but exhibit a complex pattern of impairment in higher-order cognition, showing poor decision-making and impaired emotional processing. Moreover, NT1 patients show increased creative abilities. Assessing and monitoring cognitive impairments experienced by CDH patients will allow the design of personalized interventions, parallel to pharmacological treatment, aimed at improving daytime functioning and quality of life of these patients.